Cyproheptadine as Growth Promoter In Broiler Chickens - AL-Azawi, Tahani S. S. (The Iraqi Journal of Veterinary Medicine, 2003)
Cyproheptadine hydrochloride is a very high potent histamine and serotonine antagonist. This study was conducted to investigate the role of cyproheptadine on feed intake, body weight gain, feed conversion ratio, serum total protein, cholesterol and glucose. Red blood cells (RBC), Hemoglobin (Hb), Packed Cell Volume (PCV) and differential leukocytic count in blood of chickens were also estimated. A total of 60 one-day-old Fabro chicks were randomly divided into 2 groups. One group was received cyproheptadine at a rate of 10 ug / 100g body weight daily for eight weeks and the second group was used as a control. The results revealed that cyproheptadine could stimulate feed intake and improve body weight gain in chickens. Erythrocyte count, hemoglobin content and PCV where increased significantly in these chickens accompanied by an increase in percentage of lymphocytes with a significant decrease in percentage of heterophiles and H / L ratio. This drug also reduces the total protein, cholesterol and glucose in serum.